RISKSmart Learning System Training 2024 - Norhayati, Rosli (UMPSA, 2024)
The RISKSmart Learning System Training for Kaneka’s RBI Team was held on May 16, 2024, at Kaneka Training Centre, Gebeng. The trainers are the RBI research team from the Centre for Mathematical Sciences, Assoc. Prof. Dr. Norhayati Binti Rosli, Mr. Khairul Hafiz Bin Khairuldin, Assoc. Prof. Dr. Noryanti Binti Muhammad, and Dr. Norhafizah Md Sarif.